2017
DOI: 10.1002/2017jb014456
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of induced seismicity mitigation: Numerical modeling of wastewater injection near Greeley, Colorado

Abstract: Mitigation of injection‐induced seismicity in Greeley, Colorado, is based largely on proximity of wastewater disposal wells to seismicity and consists of cementation of the bottom of wells to eliminate connection between the disposal interval and crystalline basement. Brief injection rate reductions followed felt events, but injection rates returned to high levels, >250,000 barrels/month, within 6 months. While brief rate reduction reduces seismicity in the short term, overall seismicity is not reduced. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Maximum ΔP varies from 0.04 to 42.6 MPa. This is consistent with other site-specific pore pressure models of induced seismicity (e.g., Brown et al, 2017;Healy et al, 1968;Hornbach et al, 2015;Keranen et al, 2014;Nakai et al, 2017;Ogwari et al, 2018;Ogwari & Horton, 2016). Low permeability generates the largest pore pressure increase, but pore pressure does not diffuse very far into the basement or laterally (Figure 2b); high permeability generates much further diffusion of pore pressure increase, but the magnitude of the increase is much smaller (Figure 2d) than low and medium permeability simulations (Figures 2b and 2c).…”
Section: Pore Pressure Modeling Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Maximum ΔP varies from 0.04 to 42.6 MPa. This is consistent with other site-specific pore pressure models of induced seismicity (e.g., Brown et al, 2017;Healy et al, 1968;Hornbach et al, 2015;Keranen et al, 2014;Nakai et al, 2017;Ogwari et al, 2018;Ogwari & Horton, 2016). Low permeability generates the largest pore pressure increase, but pore pressure does not diffuse very far into the basement or laterally (Figure 2b); high permeability generates much further diffusion of pore pressure increase, but the magnitude of the increase is much smaller (Figure 2d) than low and medium permeability simulations (Figures 2b and 2c).…”
Section: Pore Pressure Modeling Resultssupporting
confidence: 89%
“…The ΔCSS is shown in Figure 3 for average depth of the earthquakes, ranging from 3.8 to 4.3 km (Table S3), and in the direction of slip of the source fault. There are areas of positive ΔCSS in all scenarios that are as large as or larger than estimated triggering thresholds of pore pressure (~0.07 to 0.10 MPa) from site-specific studies (e.g., Brown et al, 2017;Keranen et al, 2014). Maximum ΔCSS at average depth varies from approximately 12 to 770 MPa in strike-slip fault scenarios (Figures 3a-3c) and approximately 18 to 62 MPa in normal fault scenarios (Figures 3d-3f).…”
Section: Coulomb Static Stress Modeling Resultsmentioning
confidence: 84%
“…MODFLOW is the USGS's modular finite‐difference hydrologic model. It is commonly used for pore pressure simulation due to its flexibility and speed (e.g., Zhang et al, 2013, 2016; Keranen et al, 2014; Hornbach et al, 2015; Ogwari & Horton, 2016; Ogwari et al, 2018; Brown et al, 2017; Brown & Ge, 2018; Goebel et al, 2017; Nakai et al, 2017; Hearn et al, 2018). It solves the three‐dimensional movement of ground water of constant density in heterogenous and anisotropic porous media (from Harbaugh, 2005): x)(Kxxhx+y)(Kyyhy+z)(Kzzhz+W=Ssht where K xx , K yy , and K zz are the principal components of hydraulic conductivity, S s is the specific storage, W is the volumetric flux per unit volume representing sources of fluid, h is hydraulic head, and t is time.…”
Section: Methodsmentioning
confidence: 99%
“…One landmark modeling study found that several high-rate SWD wells in southeast Oklahoma City produced a fluid pressure front that accurately matched earthquake hypocenter locations leading up to the Jones earthquake swarm 8 . This history-matching approach was repeated in more recent studies linking SWD operations to earthquake occurrence, e.g., in Milan, Kansas 9 , Greeley, Colorado 10 , Fairview, Oklahoma 11 , Dallas-Fort Worth, Texas 12 , and Guthrie, Oklahoma 13 . Based on the success of this history-matching approach, groundwater models are now being incorporated into seismic hazard assessments to simulate fluid pressure decay following SWD volume reductions 1417 .…”
Section: Introductionmentioning
confidence: 99%